SdsA polymorph isolation and improvement of their crystal quality using nonconventional crystallization techniques. (1st October 2015) - De la Mora, Eugenio; Flores‐Hernández, Edith; Jakoncic, Jean; Stojanoff, Vivian; Siliqi, Dritan; Sánchez‐Puig, Nuria; Moreno, Abel
<x xml:space="preserve">Abstract</x> SdsA, a sodium dodecyl sulfate hydrolase, from Pseudomonas aeruginosa was crystallized in three different crystal polymorphs and their three‐dimensional structure was determined. The different polymorphs present different crystal packing habits. One of the polymorphs suggests the existence of a tetramer, an oligomeric state not observed previously, while the crystal packing of the remaining two polymorphs obstructs the active site entrance but stabilizes flexible regions of the protein. Nonconventional crystallization methods that minimize convection, such as counterdiffusion in polyvinyl alcohol gel coupled with the influence of a 500 MHz (10.2 T) magnetic field, were necessary to isolate the poorest diffracting polymorph and increase its internal order to determine its structure by X‐ray diffraction. The results obtained show the effectiveness of nonconventional crystallographic methods to isolate different crystal polymorphs.